(untitled) - Kellerman, Jonathan (New York, 2003)
Devastated and suspected by the police after the brutal murder of his girlfriend, psychologist Jeremy Carrier finds himself engaged in a game of cat and mouse when additional murders take place and clues begin appearing in his mail.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy